Sexual Quality of Life in Gender-Dysphoric Adults Before Genital Sex Reassignment Surgery. (1st January 2015) - Bartolucci, Constanza; Gómez-Gil, Esther; Salamero, Manel; Esteva, Isabel; Guillamón, Antonio; Zubiaurre, Leire; Molero, Francisca; Montejo, Angel L.
ABSTRACT: Introduction: Although there is literature on sexuality in gender dysphoria, few studies have been done prior to genital sex reassignment surgery (SRS). Aims: To evaluate the perception of sexual QoL in gender-dysphoric patients before genital SRS and the possible factors associated to this perception. Methods: The final sample consisted of 67 male-to-female and 36 female-to-male gender-dysphoric adults consecutively attended in a gender unit who had not undergone genital SRS; 39.8% was receiving cross-sex hormonal treatment, and 30.1% had undergone breast augmentation or reduction. Sexual QoL was assessed using the sexual activity facet of the World Health Organization Quality of Life (WHOQOL)-100. Sociodemographic (age, gender, partner relationship) and clinical data (being on hormonal treatment and having undergone any breast surgery) were recorded from the clinical records. Depressive symptoms were assessed using the negative feelings facet of the WHOQOL-100. Personality was assessed using the Revised NEO-Five Factor Inventory. Main Outcome Measures: Sexual QoL, negative feelings, hormonal treatment, partner relationship, personality. Results: The mean score of the sexual facet was 10.01 (standard deviation = 4.09). More than 50% of patients rated their sexual life as "poor/dissatisfied" or "very poor/very dissatisfied, " around a quarter rated it as "good/satisfied" or "very good/very satisfied, " and the rest had a neutral perception. Three variables were significantly associated with a better sexual QoL: less negative feelings (β = −0.356; P  < 0.001), being on hormonal treatment (β = 0.216; P  = 0.018), and having a partner (β = 0.206; P  = 0.022). Age, sex, having undergone some breast surgery, and personality factors were not associated with their perception. Conclusion: This study indicates that before genital SRS, about half of gender-dysphoric subjects perceived their sexual life as "poor/dissatisfied" or "very poor/very dissatisfied." Moreover, receiving hormonal treatment, low negative feelings, and having a partner are related to a better subjective perception of sexual QoL.